2008
DOI: 10.1002/jso.21156
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of androgen receptor detection in operable breast cancer

Abstract: Methods that can detect AR localized in the cytoplasm yield important prognostic information, and further studies in patients with operable breast cancer are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 42 publications
2
13
0
2
Order By: Relevance
“…In the former, a strong better prognostication was conferred by AR positivity among patients with ER þ breast cancer both in univariate and multivariate analysis, which is in line with previously published studies (8,9,11,41,42,53). Preclinical evidence suggesting an AR-ER cross-talk also support these findings, indicating that AR can antagonize ER signaling depending on the relative levels of these two steroid receptors (2).…”
Section: Discussionsupporting
confidence: 87%
“…In the former, a strong better prognostication was conferred by AR positivity among patients with ER þ breast cancer both in univariate and multivariate analysis, which is in line with previously published studies (8,9,11,41,42,53). Preclinical evidence suggesting an AR-ER cross-talk also support these findings, indicating that AR can antagonize ER signaling depending on the relative levels of these two steroid receptors (2).…”
Section: Discussionsupporting
confidence: 87%
“…The majority of studies investigating the relationship between AR levels in the primary tumour, clinical characteristics and disease outcome have found that AR expression is a favourable prognostic indicator (reviewed by Hickey et al (2012)). In cohorts not selected on the basis of estrogen receptor-a (ERa (ESR1)) status, AR positivity has been associated with longer relapse-free, metastasis-free and overall survival, smaller tumour size and lower histological grade (Bryan et al 1984, Langer et al 1990, Kuenen-Boumeester et al 1992, Soreide et al 1992, Schippinger et al 2006, Agrawal et al 2008, Gonzalez et al 2008, Hanley et al 2008, Ogawa et al 2008, Soiland et al 2008, Park et al 2010, Yu et al 2011, Peters et al 2012, Honma et al 2013. High AR levels have also been associated with a favourable response to chemotherapy and hormonal therapy, including antioestrogens, aromatase inhibitors and progestins (Teulings et al 1980, Bryan et al 1984, Birrell et al 1995, Agrawal et al 2008, Chintamani et al 2010, Chanplakorn et al 2011, Loibl et al 2011.…”
Section: Prognostic Value Of Ar Expression In Breast Cancermentioning
confidence: 99%
“…High AR levels have also been associated with a favourable response to chemotherapy and hormonal therapy, including antioestrogens, aromatase inhibitors and progestins (Teulings et al 1980, Bryan et al 1984, Birrell et al 1995, Agrawal et al 2008, Chintamani et al 2010, Chanplakorn et al 2011, Loibl et al 2011. Importantly, AR has also been shown to be an independent predictor of relapse-free, metastasis-free and/or overall survival in some studies (Soreide et al 1992, Gonzalez et al 2008, Soiland et al 2008, Yu et al 2011. However, other studies have shown that AR levels do not predict the response to endocrine therapy or relapse-free or overall survival (Allegra et al 1979, Soreide et al 1992, Carreno et al 2007.…”
Section: Prognostic Value Of Ar Expression In Breast Cancermentioning
confidence: 99%
“…A number of studies have investigated the prognostic potential of AR expression in BCs, with the majority finding the AR to be associated with favourable clinicopathological features. In ERa-positive BCs, AR has been found to correlate with lower grade, reduced lymph node involvement and longer disease-free survival, and this correlation is proportional to the levels of AR expression (Schippinger et al 2006, Søiland et al 2008, Castellano et al 2010, Hu et al 2011, Park et al 2011, Tsang et al 2014. In one study, AR and ERa levels were analysed in 1467 BC tumours from postmenopausal women enrolled in the Nurses' Health Study (Hu et al 2011).…”
Section: Ar As a Prognostic Factormentioning
confidence: 99%